A Decade of Mozambique : Politics, Economy and Society 2004-2013 - Hanlon, Joseph. (Middle East and Islamic Studies E-Books Online, Collection 2015, ISBN: 9789004287464., 2015)
This chronology for 2004 to 2013 compiles the chapters on Mozambique previously published in the Africa Yearbook. Politics, Economy and Society South of the Sahara . The country has over the years remained one of the poorest, and poverty is not declining. But the discovery of huge gas fields could bring changes by the mid 2020s. During the period under review, the sheen began to fade from Mozambique's status as a donor darling, as donors increasingly objected to corruption while government was angered by donor impositions and took an increasingly autonomous line. The former liberation movement Frelimo remains the predominant party and has won all national elections, while two presidents have stepped down after two terms. The main opposition party Renamo retains an armed wing launching small military actions. A second opposition party gained control of four cities. A younger and better-educated generation that remembers neither the liberation struggle nor the 1982-92 civil war is beginning to challenge the established leadership.